Pratinjau Ukuran Meja dan Kursi Anak Sekolah Menurut Acuan SNI Berdasarkan Dimensi Tubuh Siswa Kelas Satu Sekolah Dasar di DKI Jakarta - Yanto, Yanto (Metris: Jurnal Sains dan Teknologi, 2018)
This paper presents a preliminary review of dimensions school furniture which was issued by National Standardization Agency of Indonesia (NSAI) through SNI 7555.4.2009 and SNI 7555.19.2011. The dimensions of seat height of chair and desk height of desk were assessed by using students’ anthropometry i.e. popliteal height and elbow rest height. Anthropometric data of 64 elementary school students of grade 1 were taken. Results showed that 97.1% boys and 96.7% girls did not match with lower level of seat height. Meanwhile, none of students in Grade 1 matched with the higher level of seat height. Similarly, 100% mismatch was found for desk height either for lower or upper level. This findings could lead to a broader study involving more samples, age group and geographical areas.